2021
DOI: 10.1002/rcm.9071
|View full text |Cite
|
Sign up to set email alerts
|

Development of an inverse low‐temperature plasma ionization source for liquid chromatography/mass spectrometry

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The results showed that for the TPI, argon provided signal responses around 2 times higher than those obtained with helium for all the analytes. Although helium is generally recommended as discharge gas, these results are in agreement with those obtained by Brecht et al using the iLTP source for LC–MS/MS measurements. After selecting argon as discharge gas, the flow rate was optimized from 100 to 400 mL min –1 achieving the highest responses at 200 mL min –1 (SI Figure S2).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that for the TPI, argon provided signal responses around 2 times higher than those obtained with helium for all the analytes. Although helium is generally recommended as discharge gas, these results are in agreement with those obtained by Brecht et al using the iLTP source for LC–MS/MS measurements. After selecting argon as discharge gas, the flow rate was optimized from 100 to 400 mL min –1 achieving the highest responses at 200 mL min –1 (SI Figure S2).…”
Section: Resultssupporting
confidence: 90%
“…Helium is usually preferred as discharge gas in soft ionization plasma sources showing an ionization mechanism which starts by the Penning ionization of the N 2 by means of He M followed by a typical APCI-like mechanism. 15 In contrast, the ionization mechanism with argon, which has recently shown a good performance by LC−iLTP-MS/MS, 25 is still not fully understood. The ignition of both gases (200 mL min −1 ) was conducted by applying square-wave high voltage pulses of +2.5 kV, a frequency of 12.5 kHz and a pulse width of 2 μs.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation